Determining HIV risk for Adolescent Girls and Young Women (AGYW) in relationships with "Blessers" and age-disparate partners: a cross-sectional survey in four districts in South Africa - Gavin George; Sean Beckett; Tarylee Reddy; Kaymarlin Govender; Cherie Cawood; David Khanyile; Ayesha B. M. Kharsany (BMC, 2022)
Abstract Background HIV incidence among adolescent girls and young women (AGYW) remains high, with their male partners a prominent factor in sustaining these elevated rates. Partnership characteristics remain important metrics for determining HIV risk, with evidence indicating that AGYW engaged in transactional and age-disparate relationships face greater HIV exposure. This study examines the risk posed to AGYW in a relationship with a "Blesser", defined as male who provides his female partner with their material needs or desires in exchange for a sexual relationship, an age-disparate (5 or more years older) partner, and the potential compounded risk of being a relationship with a partner or partners who are considered both a "Blesser" and age-disparate. Methods A cross -sectional household based representative sample of AGYW (aged between 12-24 years) were enrolled in the study (n = 18 926) from the districts of City of Johannesburg and Ekurhuleni in the Gauteng province and the Districts of eThekwini and uMgungundlovu in the province of KwaZulu-Natal (KZN) in South Africa between March 13, 2017 to June 22, 2018. Participants completed a structured questionnaire and provided finger-prick blood samples for laboratory measurements. Our analysis used descriptive statistics and multiple binary logistic regressions accounting for survey weights, clustering and stratification. Findings The median age of the sample was 21 years old (Interquartile range: 19-23) and nearly three quarters (73.7%) were currently attending school. Whilst all relationships exposed AGYW to potential HIV risk, multiple binary logistic regression analysis revealed that AGYW in a relationship with both a Blesser and an age-disparate partner were more likely to be HIV positive (AOR: 3.12, 95% CI: 1.76-5.53, p < 0.001), diagnosed with an STI (AOR: 4.60, 95% CI: 2.99-7.08, p < 0.001), had 2 or more sexual partners in the previous 12 months (AOR: 6.37, 95% CI: 3.85-10.54, p < 0.001), engaged in sexual activity at age 15 or younger (AOR: 3.67, 95% CI: 2.36-5.69, p < 0.001) and more likely to have ever been pregnant (AOR: 2.60, 95% CI: 1.24-5.45, p < 0.05) than those not in a relationship with either a Blesser or age-disparate partner. Conclusion Different relationships present different HIV risk to AGYW. AGYW who had engaged in relationships with both a Blesser and an age-disparate partner were at greater HIV risk when examined against these relationships independent of one another. The data reveals the compounded HIV risk of being in both a transactional and age-disparate relationship.